The Relationship Between Height and Diameter of Palaquium Obtusifolium Burck Trees at 7 Years of Age - Ifert Ehrlick Tudon (Politeknik Pertanian Negeri Samarinda, 2025)
The relationship between tree height and diameter is a key indicator for understanding growth patterns and the physiological balance of forest trees. In tropical agroforestry systems, this relationship is commonly used to estimate tree height, volume, and biomass without direct field measurements. This study was conducted on a seven-year-old Palaquium obtusifolium (Nantu) stand in Pandiri Village, Poso District, Central Sulawesi Province, to identify the pattern of the relationship between stem diameter and total height. Measurements were taken from 64 trees, which were measured with a Suunto clinometer and a phi tape. Data normality was tested using the Shapiro–Wilk test, and potential outliers were identified through boxplot analysis. The relationship between height and diameter was analyzed using a simple linear regression model in R Studio. The results showed a significant linear relationship between diameter and height, expressed by the equation H = 4,82 + 0,48D, with a coefficient of determination (R²) of 0,69. This indicates that approximately 69% of the variation in tree height could be explained by stem diameter. The regression model was statistically significant (p < 0,05) and could be effectively applied to estimate tree height in the field. Keywords: